Analisis Peraturan Pemerintah Nomor 2 Tahun 2014 Dan Fatwa Dusun MUI 2016 Terhadap Pelayanan Hotel Berbasis Syari’ah Di Kabupaten Asahan - Nasution, Syahrul; Nurwandri, Andri; Lestari, Inda (Mediation : Journal of Law, 2024)
It cannot be denied that the hotel industry in Indonesia is very worrying. Civil Service Police officers and the Republic of Indonesia Police often carry out raids on hotel guests who are not married couples, some who are drunk, and so on. This event is often covered by the media. However, because there are non-violent initiatives and light punishments such as administrative action and summoning parents, violators no longer feel discouraged. The authors believe that conducting research is relevant and necessary considering the issues mentioned above. Therefore, the author participated in research entitled Analysis of government Regulation Number 2 Of 2014 And Fatwa village MUI 2016 On Sharia-Based Hotel Services In Asahan District. Because the authors believe that more research is needed and is crucial regarding sharia-compliant hotel companies. Determining whether companies labeled as sharia, especially those operating in the hotel industry, truly apply sharia principles or are just symbols used to attract customers and boost profits is one of the main objectives of this research. Apart from that, the aim of this research is to find out the requirements contained in the Fatwa of the National Sharia Council-Indonesian Ulema Council No. 108/DSN-MUI/X/2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles, as well as sharia aspects of sharia hotels which can be realized in the form of goods, services and management.